Carboxyl groups do not play the major role in binding metal cations by graphene oxide. Issue 32 (5th August 2021) - Shayimova, Julia; Amirov, Rustem R.; Iakunkov, Artem; Talyzin, Alexandr; Dimiev, Ayrat M.
Abstract : Interactions of Mn 2+ ions with graphene oxides, prepared by Hummers' (HGO) and Brodie's (BGO) methods are investigated by means of the NMR relaxation. Metal ions are bound efficiently by BGO, containing a negligibly small quantity of carboxyl groups. Abstract : In this study, we investigate the chemical interactions of Mn 2+ ions with graphene oxides, prepared by Hummers' (HGO) and Brodie's (BGO) methods in aqueous solutions by means of NMR relaxation. Carboxyl groups, which are always present in HGO in significant quantities, are often considered as the main binding sites for metal ions. Here we demonstrate that metal ions are bound efficiently by BGO, containing a negligibly small quantity of carboxyl groups. The difference in the shape of the relaxation curves is due mostly to the difference in the solubility and exfoliation degree of the two GO samples in aqueous media. HGO binds Mn 2+ in the broad pH range, including highly acidic solutions, while BGO binds only at pH > 6, since it is not dispersible in water at lower pH values. The ability of BGO to chemically bind Mn 2+ despite lacking sulfate and carboxyl groups, coupled with our earlier published findings, strongly suggests that carboxyl groups do not play the main role in binding metal ions by GO, as is commonly believed. We propose that metal ions initiate a significant transformation in the GO structure to attain the most efficient coordination of metal ions. This reorganization might involve the metal cation induced C–C bond cleavage with the formation of enols at the newly formed edges.